CULTURAL TERMS IN INDONESIAN CHILDREN’S STORIES: A STUDY OF HARI ISTIMEWA SUWIDAK LORO AND MAU MASAK APA, LINTANG? - Sudirman, Eka Pratiwi; Muhajir, Fatimah (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2025)
This study examines how Indonesian cultural identity is represented and rendered in two children’s narratives, Hari Istimewa Suwidak Loro and Mau Masak Apa, Lintang?, through the identification of culture-specific lexical items and the translation strategies applied, based on Newmark’s (1988) framework. The findings indicate that material culture—particularly culinary references such as botok, klepon, and serabi—is the most prevalent category, followed by social culture, which includes kinship terms and communal practices. These categories reflect the translators’ emphasis on tangible and relational aspects of Indonesian life, suggesting that food and familial terms serve as culturally resonant vehicles for transmitting values and traditions to young readers. Six translation strategies were identified, with functional and cultural equivalence being the most frequently employed, indicating a prioritization of accessibility. Meanwhile, transference and amplification were used to preserve cultural specificity. These findings underscore the role of translation in mediating cultural representation and enhancing cross-cultural understanding through children’s literature.